Professors digital situation measurement: the case of a Colombian private university - Vega, Omar Antonio; Rodríguez Baena, Luis; Pérez Agustín, Mercedes; Melo-Solarte, Diego Samir (Revista Espacios, 2020)
This paper presents an experience addressed to determine the digital situation of professors in a Colombian Private, by integrating an index proposed by Vega, with the dimensions of digital literacy by Rangel and Penalosa that prove similar results with a few differences; as regards to handling and use of ICT by the professors. Similar tendencies observed in other institutions point out the need to establish strategies, addressed to the development of digital competences by the professors.
Medición de la situación digital de profesores: el caso de una universidad privada colombiana
Este artículo presenta una experiencia orientada a determinar la situación digital de profesores de una universidad privada colombiana, mediante la integración del índice propuesto por Vega con las dimensiones de alfabetización digital de Rangel y Peñalosa, con resultados similares a antecedentes, en cuanto a su manejo y uso de TIC. Las tendencias observadas señalan la necesidad de establecer estrategias dirigidas al desarrollo de competencias digitales por parte de los profesores.
Keywords: measurement of digital divide; University Professors; digital competence; medición de brecha digital; profesores universitarios; competencia digital; Scopus